Effect of pulsed light on shelf life of chill stored yellowfin tuna (Thunnus albacares) steaks - Ananthanarayanan, T. R.; Nithin, C. T.; C. Joseph, Toms; Bindu, J.; Srinivasa Gopal, T. K. (Indian Journal of Fisheries, 2019)
In this study, the effect of pulsed light (PL) treatment on the shelf life extension of yellowfin tuna (Thunnus albacares) steaks was investigated. Tuna steaks of 1 cm thickness weighing 80 g packed in 300 gauge cast polypropylene pouches were subjected to PL treatment using Xenon pulse light machine RC-847. The samples were stored at 2Â±1OC and analysed at specific time intervals. Shelf life studies were carried out in terms of reduction of aerobic flora as inferred from the total plate count (TPC) and the psychrophilic count. The samples were also evaluated in terms of colour (L*, a* and b*), biochemical and sensory parameters. The initial reduction as well as lower rate of increase in the microbial count on the PL treated samples clearly highlighted the efficiency of PL technology as a novel non-thermal preservation technique. Low values of chemical indicators of spoilage and better values of sensory and colour values of PL treated samples also suggested the efficacy of PL treatment in microbial inactivation. An overall extension of 13 days of shelf life was achieved for PL treated samples whereas control samples were rejected on 13th day